Copper-catalysed regioselective sulfenylation of indoles with sodium sulfinates. Issue 5 (30th May 2018) - Luo, Xiaojun; Liu, Qiang; Zhu, Hongxia; Chen, Huoji
Abstract : A copper-catalysed sulfenylation of indoles with sodium sulfinates that affords 3-sulfenylindoles in good-to-excellent yields in N, N -dimethyl formamide (DMF) is described. In the process, DMF serves not only as a solvent but also as a reductant. This transformation is easy to carry out and has mild reaction conditions and good functional group tolerance.